Combustion Characteristics of Mui and Taru Basin Coal in a Fluidized Bed Combustor. (27th May 2021) - Ondari, Brian; Siagi, Zachary; Kumar, Anil
Abstract : Coal reserves at Mui and Taru in Kitui and Kilifi counties in Kenya are estimated to provide over 400 million tons. Being new discoveries, their properties were investigated using the ASTM standards, while the combustion characteristics were studied in a fluidized bed combustor (FBC). Proximate analyses of the Mui1, Mui2, and Taru coal samples were as follows: moisture content 3.75, 5.48, and 3.53%; volatile matter 59.25, 58.05, and 55.10%; ash content 9.25, 11.48, and 24.63%; and fixed carbon 27.80, 25.00, and 16.75%, respectively. Ultimate analysis for Mui1, Mui2, and Taru coal samples is as follows: sulphur wt.% 1.94, 1.89, and 1.07; carbon 65.68, 60.98, and 51.10%; hydrogen 5.97, 5.70, and 5.09%; nitrogen 0.92, 0.94, and 1.00%; and oxygen 11.62, 12.33, and 11.13%, respectively. Temperature–weight loss analysis showed that for Mui and Taru basin coal, devolatilization starts at 200°C and 250°C, and combustion was complete at 750°C and 650°C, respectively. The maximum temperature obtained in FBC was 855°C at 700 mm height, just above the point of fuel feed, while the minimum was 440°C at height of 2230 mm. Maximum pressure drop was 1.02 mbars at 150 mm, while minimum was 0.67 mbars at 700 mm from the base. Gross calorific values were Mui1 coal, 27090 kJ/kg (grade A), Mui2 coal, 25196 kJ/kg (grade B), and the Taru coal, 21016 kJ/kg (grade C). Flue gas analysis for Taru and Mui coal gave hydrogen sulfide as 20 ppm and 6 ppm, maximum carbon monoxide of 2000 ppm at 600°C, and a decrease in oxygen as combustion progressed to a minimum of 15%, followed by an increase to 20.3%, suggesting depletion of coal. Based on the findings, the coal samples were suitable for commercial use.